The Strategic Role of the School Committee in Islamic Education at MI Al-Barkah North Sumatra - Mursal Aziz; Anggi Putri Utami; Isal Salbila; Usna Aulia (Jurnal IAI Bunga Bangsa Cirebon, 2024)
The establishment of school committees is an important strategy to strengthen community involvement in education and improve the effectiveness of school management. This research aims to investigate the process of forming and establishing committees at MI Al-Barkah. The research method used is descriptive qualitative, with data collection techniques including interviews, field observations, and documentation studies (library literature). The research results show that the committee at MI Al-Barkah has been formed since 2007 and remains active to this day. The formation and establishment of this school committee has had a positive impact in increasing parent participation, the quality of education, and the effectiveness of school management.